Variabilidade de caracteres nutricionais e de produtividade de grãos em cultivares de milho - Alves, Bruna Mendonça (2013)
This study aimed to verify whether there is genetic variability regarding nutritional and productivity characters of grains among cultivars of early cycle, very early cycle and transgenic maize and whether variability exists, discuss the differences among the cultivars, in order to select cultivars for crossing. It was used data of three experiments conducted during the harvest 2009/2010, at the experimental area of the Plant Science Department of the Federal University of Santa Maria. During these experiments were analyzed 76 maize cultivars, being 36 of early cycle, 22 of very early cycle and 18 of transgenic cultivar. In each experiment, after the harvest, in each of the three replicates of each cultivar, it was measured the following variables: grain productivity, crude protein, lysine, methionine, cysteine, threonine, tryptophan, valine, isoleucine, leucine, phenylalanine, histidine, arginine, ethere extract, starch and amylose in percentage of crude material. For each experiment, it was made an analysis of variance of each variable, according to a randomized block design. The averages of cultivars were compared by using Scott-Knott test. For each experiment was used the cluster analysis. Initially, discarding of variables was done in three steps: 1) Removal of variables without significant importance for the cultivar (F test of ANOVA), 2) Removal of variables that increase multicollinearity in the correlation matrix among the variablesand 3) Removal of variables by main components analysis. With the remaining variables was determined the Mahalanobis distance matrix (D2) and the cultivar clustering was done by using UPGMA method. Posteriorly, it was built a dendogram and calculated the cophenetic correlation coefficient. In order to test the hypothesis of differences among the average profile, for each experiment, it was calculated the evaluation of multivariate analysis of variance. There is variability among the early cycle, very early cycle and transgenic cultivars regarding grain productivity and nutritional characters in maize. Except starch which showed no variability in early cycle cultivar and transgenic cultivar, and methionine variables for transgenic cultivars. Based on variables grain productivity, crude protein and amylose, three groups were formed for early maturity cultivars, three groups for veryearly cycle cultivars and two groups for transgenic cultivars.